2013
DOI: 10.1007/s13191-013-0287-1
|View full text |Cite
|
Sign up to set email alerts
|

Force Finishing and Centering to Balance a Removable Complete Denture Prosthesis Using the T-Scan III Computerized Occlusal Analysis System

Abstract: Obtaining bilateral balance of removable complete denture prostheses is the occlusal goal of the restorative dentist or prosthodontist. Despite our best clinical efforts, and the using of advanced mechanical devices like semi-adjustable articulators and face bow transfer mounting of dental casts, it is a struggle to provide accurate occlusal force balance. Some of the advocated reasons for the clinical difficulty of obtaining reliable occlusal balance are that stone casts lack soft tissue resiliency, and artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 2 publications
3
27
0
Order By: Relevance
“…In agreement with Muller, et al test results confirmed this phenomenon that patients with mandibular implantsupported overdenture tend to acquire thicker and stronger masseter muscle than conventional denture wearers by time [16]. Masseter muscle in mandibular implant-supported overdenture patients provide more efficient mastication considering the time for complete muscle adaptation.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In agreement with Muller, et al test results confirmed this phenomenon that patients with mandibular implantsupported overdenture tend to acquire thicker and stronger masseter muscle than conventional denture wearers by time [16]. Masseter muscle in mandibular implant-supported overdenture patients provide more efficient mastication considering the time for complete muscle adaptation.…”
Section: Discussionsupporting
confidence: 78%
“…After 12 months, significant differences were reported and T-scan III group (Group II) showed to have better mastication of both chewing gums with less variance of hue. A strong correlation can be documented with studies carried by Muller, et al [16]. It was mentioned before the time factor in increasing the thickness of masseter muscle and its activity after muscle adaptation, in addition to the type of implant-supported prostheses confirming a proper occlusion in the prostheses can contribute to a better muscle of mastication performance and long term activity.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The system displays all this data into easily interpreted colour coded 2-D and 3-D graphics. 20,22 Reliability, sensibility and reproducibility of the T-scan III system has been reported by several researchers. 20, 21, 23 -26 According to Koos et al 20 , the system is reliable (97.2%) and considerably accurate (98%) for intra-oral use and everyday clinical practice with a measurement error of 1%.…”
Section: Introductionmentioning
confidence: 97%